2014
DOI: 10.1242/jeb.092288
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of theRana sylvaticabrevinin-1SY antimicrobial peptide during development and in dorsal and ventral skin in response to freezing, anoxia, and dehydration

Abstract: Brevinin-1SY is the only described antimicrobial peptide (AMP) of Rana sylvatica. As AMPs are important innate immune molecules that inhibit microbes, this study examined brevinin-1SY regulation during development and in adult frogs in response to environmental stress. The brevinin-1SY nucleotide sequence was identified and used for protein modeling. Brevinin-1SY was predicted to be an amphipathic, hydrophobic, alpha helical peptide that inserts into a lipid bilayer. Brevinin-1SY transcripts were detected in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
0
17
0
1
Order By: Relevance
“…However, apparent gene duplications allow for gradual genetic changes that appear to be positively selected in response to pathogens ( Tennessen and Blouin, 2007 ). Defensive AMPs appear to be released constitutively into the mucus at low concentrations, but they can be increased significantly when the amphibian hosts are alarmed or injured ( Pask et al, 2012 ) and can be affected by environmental stressors ( Katzenback et al, 2014 ). However, some amphibians appear to lack the capacity to produce conventional cationic AMPs ( Conlon, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, apparent gene duplications allow for gradual genetic changes that appear to be positively selected in response to pathogens ( Tennessen and Blouin, 2007 ). Defensive AMPs appear to be released constitutively into the mucus at low concentrations, but they can be increased significantly when the amphibian hosts are alarmed or injured ( Pask et al, 2012 ) and can be affected by environmental stressors ( Katzenback et al, 2014 ). However, some amphibians appear to lack the capacity to produce conventional cationic AMPs ( Conlon, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies used transmission electron microscopy to examine discharge of granular glands (Delfino et al ., 2006). Other studies used northern blotting, in situ hybridization or RT-PCR to detect mRNAs encoding AMPs (Clark et al ., 1994; Reilly et al ., 1994; Iwamuro et al ., 2006; Katzenback et al ., 2014). As none of these studies demonstrated secretion of active peptides from living tadpoles, we chose to use direct MALDI-TOF MS to examine AMP expression on tadpoles (Chaurand et al ., 1999; Woodhams et al ., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that wood frogs can tolerate up to 48 hours of anoxia exposure at 5°C with no mortality . In addition, previous studies have investigated the effects of exposure to 24‐hour anoxia and 4 hours of aerobic recovery on metabolic rate depression in different wood frog tissues . As such, the current study uses the same treatment conditions to build on previous studies that focus on understanding the regulation of metabolic rate depression over the anoxia/reoxygenation cycle.…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, previous studies have investigated the effects of exposure to 24-hour anoxia and 4 hours of aerobic recovery on metabolic rate depression in different wood frog tissues. 1,5,13,[53][54][55] As such, the current study uses the same treatment conditions to build on previous studies that focus on understanding the regulation of metabolic rate depression over the anoxia/reoxygenation cycle. Both liver and skeletal muscle contain glycogen that can be used to generate glucose to sustain glycolysis under anaerobic conditions.…”
mentioning
confidence: 99%